Improving the Energetic Properties of Dinitropyrazoles by Utilization of Current Concepts. Issue 37 (20th September 2018) - Bölter, Marc F.; Klapötke, Thomas M.; Kustermann, Tessa; Lenz, Tobias; Stierstorfer, Jörg
Abstract : The syntheses of two different isomeric dinitropyrazole N ‐oxides are described and compared to each other. 3, 4‐Dinitropyrazole‐1 N ‐oxide (2 ) and 3, 5‐dinitropyrazole‐1 N ‐oxide (4 ) were used, and four different nitrogen‐rich salts were synthesized in order to enhance performance and sensitivity values. Furthermore, two methylene‐bridged isomeric dinitropyrazoles were synthesized by using diiodomethane. The obtained compounds were characterized by using low‐temperature single‐crystal X‐ray diffraction, IR spectroscopy, multinuclear NMR spectroscopy, mass spectrometry, elemental analysis and DSC measurements. The bridged compounds show a high thermal stability ( T dec. : 319 °C and 330 °C) whereas the ionic compounds display lower values ( T dec. : 131 °C–266 °C). Furthermore, the sensitivity values toward impact, friction and electrostatic discharge were determined according to standard methods. Their sensitivity values lie in the range of 5 to 40 J for impact and 216 to 360 N for friction. Adapted from recalculated X‐ray densities and calculated heat of formation values, the energetic performances were computed by using the EXPLO5 code. They support the high energetic character of the title compounds. The values ( V D : 7909–8279 m s –1 ; p CJ : 242–282 kbar) of the salts and bridged pyrazoles ( V D : 7966 and 8140 m s –1 ; p CJ : 263 and 280 kbar) were compared to RDX. Abstract : Three different concepts ( N ‐oxidation, methylene bridging and salt formation) for the functionalization of two isomeric dinitropyrazoles were used to tune the energetic properties and sensitivity values. The compounds show high thermal stabilities and reasonable energetic performances.